2014
DOI: 10.3389/fnbeh.2014.00004
|View full text |Cite
|
Sign up to set email alerts
|

Neurosonological Examination: A Non-Invasive Approach for the Detection of Cerebrovascular Impairment in AD

Abstract: There has been a growing interest in vascular impairment associated with Alzheimer's disease (AD). This interest was stimulated by the findings of higher incidence of vascular risk factors in AD. Signs of vascular impairment were investigated notably in the field of imaging methods. Our aim was to explore ultrasonographic studies of extra-and intracranial vessels in patients with AD and mild cognitive impairment (MCI) and define implications for diagnosis, treatment, and prevention of the disease. The most fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 100 publications
(123 reference statements)
0
16
0
Order By: Relevance
“…Several findings have been done [181]. Silvestrini et al [182] found out an increased carotid intima-media thickness (IMT), which is a parameter of the arterial wall, in AD patients compared to healthy subjects.…”
Section: Transcranial Doppler (Tcd) Ultrasonographymentioning
confidence: 99%
See 1 more Smart Citation
“…Several findings have been done [181]. Silvestrini et al [182] found out an increased carotid intima-media thickness (IMT), which is a parameter of the arterial wall, in AD patients compared to healthy subjects.…”
Section: Transcranial Doppler (Tcd) Ultrasonographymentioning
confidence: 99%
“…Nowadays, colour-coded duplex ultrasonography might overcome some of these drawbacks, but it offers lower performance for long monitoring. Furthermore, even if some researches suggest the possibility of using ultrasonography to distinguish between AD's symptoms from other dementias such as the VaD [193], this is not still possible [181]. Even worse, given that the relationship between vascular degeneration and dementia is not clear, it cannot even be known if this technique could really serve as a diagnosis method.…”
Section: Transcranial Doppler (Tcd) Ultrasonographymentioning
confidence: 99%
“…4 AD has heavy medical, economic and social consequences due not only to AD itself but also due to the related problems such as dementia, both dependency and disability among older people 5 and vascular impairment. 6 Although the AD-related neurodegenerative process remains unclear, 7 description of some pathogenic processes has been reported. AD is associated with the aggregation of abnormal proteins 2 including amyloid beta (Ab)protein 5,8 that aggregate into senile plaques 9 in the brains of AD patients 8 and the pathologically modified tau 9 which are hyperphosphorylated 5 and that aggregate into neurofibrillary tangles 9 in the brain.…”
Section: Introductionmentioning
confidence: 99%
“…The next three papers are clinical, Vlček and Laczó (2014) review neural correlates and spatial orientation changes in mild cognitive impairment and AD. Urbanova et al (2014) demonstrate an intriguing potential of neurosonology as a non-invasive approach for detecting cerebrovascular disruptions associated with AD, and Marciniak et al (2014) review beneficial changes in meditation on the cognitive functions associated with aging and neurodegeneration.Another section is dedicated to depression, which is also accompanied by subtle cognitive deficits, although more pronounced disruptions are seen in the mood and motivation. A theory paper by Nekovarova et al (2014b) discusses the relation between depression and pain and raises an interesting question, whether antidepressants may also act as analgesics.…”
mentioning
confidence: 99%
“…The next three papers are clinical, Vlček and Laczó (2014) review neural correlates and spatial orientation changes in mild cognitive impairment and AD. Urbanova et al (2014) demonstrate an intriguing potential of neurosonology as a non-invasive approach for detecting cerebrovascular disruptions associated with AD, and Marciniak et al (2014) review beneficial changes in meditation on the cognitive functions associated with aging and neurodegeneration.…”
mentioning
confidence: 99%